Pelatihan Pemanfaatan Baterai Lithium-ion dengan Sistem Manajemen Baterai (BMS) sebagai Solusi Energi Cadangan - Yusuf Nurul Hilal; Titik Nurhayati; Budiana Destyningtias; Isya' Aryan S; Harmini (Universitas Muria Kudus, 2026)
This community service activity aims to equip 15 participants at SMK Muhammadiyah 2 Jepara with technical competencies in assembling a backup energy system. The novelty of this article lies in the application of Lithium-Ion battery technology integrated with a smart Battery Management System (BMS) as a more efficient and safer power storage solution compared to conventional lead-acid batteries, as well as the implementation of a hands-on training method. This five-hour program successfully guided participants through the process of assembling Lithium-Ion battery cells and integrating them with a BMS to achieve optimal functionality. The results demonstrate that the assembled battery unit, when connected to an inverter, is capable of providing a stable power supply to various electronic loads, including mobile phone chargers, laptops, and active speakers. The final conclusion of this activity is that the participants have successfully mastered modern energy storage technology while producing a functional backup energy system ready to support emergency electrical needs within the school environment.